2015
DOI: 10.1093/mnras/stv1161
|View full text |Cite
|
Sign up to set email alerts
|

The mass spectrum of compact remnants from the parsec stellar evolution tracks

Abstract: The mass spectrum of stellar-mass black holes (BHs) is highly uncertain. Dynamical mass measurements are available only for few (∼ 10) BHs in X-ray binaries, while theoretical models strongly depend on the hydrodynamics of supernova (SN) explosions and on the evolution of massive stars. In this paper, we present and discuss the mass spectrum of compact remnants that we obtained with SEVN, a new public populationsynthesis code, which couples the PARSEC stellar evolution tracks with up-to-date recipes for SN exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
385
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(408 citation statements)
references
References 104 publications
21
385
1
1
Order By: Relevance
“…This result is in agreement with other studies, like, e.g. [53]. On the contrary, models with initial masses lower than ∼ 60 M ⊙ , at all metallicities, can easily produce black holes with the typical masses associated to GW151226.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with other studies, like, e.g. [53]. On the contrary, models with initial masses lower than ∼ 60 M ⊙ , at all metallicities, can easily produce black holes with the typical masses associated to GW151226.…”
Section: Discussionsupporting
confidence: 93%
“…We speculate that this could represent the dynamical environment of an early collapse associated with the formation of a dense stellar system, such as a GC (e.g. Mapelli et al 2013;Mapelli & Zampieri 2014;Ziosi et al 2014;Spera et al 2015;Kimpson et al 2016). For this scenario we study the cumulative number of BBH mergers forming through the GW inspiral channel, N Iij , relative to that of the post-interaction binary merger channel, N Mij , as a function of time τ = t − t 0 .…”
Section: Early-burst Scenariomentioning
confidence: 99%
“…They found that they shed most of their mass via winds and are expected to end their lives as BHs less massive than ∼ 150 M . At low metallicity, instead, mass loss due to winds is much reduced, thus increasing the mass of the final remnant (Heger et al 2003;Vink 2008;Mapelli, Colpi & Zampieri 2009;Belczynski et al 2010;Mapelli et al 2013;Spera, Mapelli & Bressan 2015). A BH seed of 10 3 M can be formed in this "nuclear cluster" scenario (Omukai, Schneider & Haiman 2008;Devecchi & Volonteri 2009;Regan & Haehnelt 2009;Katz, Sijacki & Haehnelt 2015).…”
Section: Introductionmentioning
confidence: 99%